Papers for the Copenhagen Workshop on Open Biblical Resources - Winther-Nielsen, Nicolai (HIPHIL Novum, 2019)
A workshop on open resources for the original languages of the Bible in Copenhagen in March 2018 was the start of a new Copenhagen Alliance for Open Biblical Resources. The point of departure for the workshop was the need for programs and applications like Paratext and Bible Online Learner to have access to high-quality and reliable open data in order to assist Bible translators, teachers and students of Biblical Hebrew and New Testament Greek. The publication of contributions presents papers on methods for annotation, resources tracing patristic quotations and data for detached constructions in Biblical Hebrew. Reports cover tasks and data for Bible translation and research, treebanks, and applications like STEPBible and Bible Online Learner.